A straightforward trail study on analysis of thickness variation of black nickel coating on stainless steel surface for emissivity. (2021) - Karthick, S.; Prasanna Raj Yadav, S.; Joel, C.; Senthilnathan, K.; Suresh, Ramya; Muthukumaran, S.
Abstract: The most important significant renewable energy for power production is solar radiation. In solar products emissivity of the material used create more impact on performance. So this investigation study about the emissivity of black nickel coated stainless steel surfaces by varying the thickness of the coating. In this study three different thickness of coating are considered for investigating such as 0.2 mm, 0.3 mm and 0.4 mm of black nickel coating. In each thickness have three different heats such as 150 W, 180 W and 210 W are the input for identification of surface temperature of the black body and black nickel coated body.